Paediatric emergency department dog bite attendance during the COVID-19 pandemic: an audit at a tertiary children's hospital - Carri Westgarth; Robert M Christley; John S P Tulloch; Simon Minford; Vicky Pimblett; Matt Rotheram (BMJ Publishing Group, 2021)
Background Responses to the COVID-19 pandemic include strict public health measures, such as national lockdowns. During these measures, paediatric emergency department attendances have declined and the prevalence of presenting complaints has changed. This study sought to identify whether dog bite attendance and victim demographics changed during COVID-19 public health measures.Methods An audit was conducted of emergency department attendance data from a UK tertiary paediatric hospital between January 2016 and September 2020. Dog bite attendance and victim demographics were explored using χ2 tests and multivariable Poisson regression. The mean monthly percentage of attendance due to dog bites in 2020 was compared against predicted percentages based on previous years' data.Results Dog bite attendance rose in conjunction with the introduction of COVID-19 public health measures and reached a peak in July 2020 (44 dog bites, 1.3% of all attendances were due to dog bites). This was a threefold increase in dog bite attendance. By September 2020, attendance had returned to normal. The demographic profile of child dog bite victims remained the same. Boys had the highest attendance rates in 7-12 year-olds, girls in 4-6 year-olds. Girls showed higher attendance rates in the summer, while boys' attendance rates were constant throughout the year. COVID-19 public health measures were associated with a 78% increase in attendance for boys and a 66% increase in girls.Conclusions COVID-19 national public health measures were associated with an increase in paediatric emergency department dog bite attendance, and may be due to increased child exposure to dogs via 'stay at home' orders and school closures. National lockdowns are likely to continue globally throughout the COVID-19 pandemic; this is likely to result in more dog bites. Urgent public health communication and injury prevention strategies are needed to help prevent these avoidable injuries.